2016
DOI: 10.3390/v8060153
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Molecular Variability Studies Reveal a New Genetic Clade of Citrus leprosis virus C

Abstract: Citrus leprosis virus C (CiLV-C) causes a severe disease affecting citrus orchards in the Western hemisphere. This study reveals the molecular variability of the virus by analyzing four genomic regions (p29, p15, MP and RNA2-intergenic region) distributed over its two RNAs. Nucleotide diversity (π) values were relatively low but statistically different over the analyzed genes and subpopulations, indicating their distinct evolutionary history. Values of πp29 and πMP were higher than those of πp15 and πRNA2–IR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
23

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 70 publications
4
41
0
23
Order By: Relevance
“…We have previously showed that CiLV-C is able to infect Arabidopsis, inducing localized chlorotic symptoms upon infestation with Brevipalpus viruliferous mites (Arena et al, 2013;Ramos-González et al, 2016). In Arabidopsis, symptoms of CiLV-C infection occur in approximately 1/3 of the time they appear in sweet orange (Citrus sinensis), the virus' natural host.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously showed that CiLV-C is able to infect Arabidopsis, inducing localized chlorotic symptoms upon infestation with Brevipalpus viruliferous mites (Arena et al, 2013;Ramos-González et al, 2016). In Arabidopsis, symptoms of CiLV-C infection occur in approximately 1/3 of the time they appear in sweet orange (Citrus sinensis), the virus' natural host.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis thaliana appears as the primary alternative host model for plant-pathogen interaction studies, benefiting from a high-quality curated genome and several resources for reverse genetics approaches (Nishimura and Dangl, 2010). Recently, we reported Arabidopsis as experimental host for Citrus leprosis virus C (CiLV-C), a BTV-C (Arena et al, 2013;Ramos-González et al, 2016). In this work, Arabidopsis plants were assessed for their capacity to host a wider range of BTV including another BTV-C, Solanum violaefolium ringspot virus (SvRSV), and two BTV-N, Coffee ringspot virus (CoRSV) and Clerodendrum chlorotic spot virus (ClCSV) .…”
Section: Introductionmentioning
confidence: 99%
“…Mites were transferred to an area of approximately 4 cm in diameter of the fruit surrounded by a barrier of the pest adhesive Biostop gum (Biocontrole, Indaiatuba, Brazil) prepared with a wet mixture of wheat flour, plaster, and fine sand (1:1:2) (Rodrigues et al, 2007). Viruliferous mites were obtained by rearing the non-viruliferous mites from “Tahiti” acid lime as described above on sweet oranges fruits collected from a citrus grove with high incidence of leprosis caused by the CiLV-C strain SJP (Ramos-González et al, 2016) in São José do Rio Preto, State of São Paulo, Brazil. Mites from both viruliferous and non-viruliferous populations were reared for several generations and periodically evaluated for the presence of CiLV-C by RT-PCR using primer pairs designed for a region within the CiLV-C MP gene (Locali et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…(Weeks et al, 2001). Within the group of Brevipalpus species that transmit plant viruses, B. yothersi (synonym B. phoenicis Geijskes citrus type) is the main vector of the cileviruses (Beard et al, 2015; Sánchez-Velázquez et al, 2015; Ramos-González et al, 2016). Once acquired during any of the active phases of these mites, CiLV-C is persistently transmitted to distant parts within the same plant and to new ones, but not to their offspring (Bastianel et al, 2010; Kitajima and Alberti, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se atualmente que algumas linhagens de B. yothersi (tanto de citros quanto de cafeeiro) mantidas em laboratório no Instituto Biológico e no Centro de Citricultura do IAC, apresentam a capacidade de aquisição e transmissão de vírus, tanto da leprose dos citros quanto da mancha anular do cafeeiro (Ramos- González et al, 2016González et al, , 2017Nunes et al, 2017).…”
Section: Novas Abordagens Sobre O Complexo B Phoenicisunclassified